2017
DOI: 10.1155/2017/7959154
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium avium Subsp. paratuberculosis Induces Specific IgE Production in Japanese People with Allergies

Abstract: Background. The prevalence of allergies is steadily increasing worldwide; however, the pathogenesis is still unclear. We hypothesized that Mycobacterium avium subsp. paratuberculosis (MAP) may contribute to allergy development. This organism can be present in dairy foods, it can elicit an immunomodulatory switch from a Th1 to a Th2 response, and it has been speculated that it is linked to several human autoimmune diseases. To determine the contribution, sera from 99 individuals with various atopic disorders an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Individuals exposed to Mycobacterium tuberculosis or Mycobacterium avium Subsp. Paratuberculosis infection generated IgE responses [32,33]. Although mycobacterial antigen is generally considered to downregulate IgE production [34], our and others' results implied that some mycobacterium including BCG Lymphocytes from the spleens and MLNs were stimulated with 10 μg/ml ConA or 10 μg/ml OVA.…”
Section: Discussionmentioning
confidence: 53%
“…Individuals exposed to Mycobacterium tuberculosis or Mycobacterium avium Subsp. Paratuberculosis infection generated IgE responses [32,33]. Although mycobacterial antigen is generally considered to downregulate IgE production [34], our and others' results implied that some mycobacterium including BCG Lymphocytes from the spleens and MLNs were stimulated with 10 μg/ml ConA or 10 μg/ml OVA.…”
Section: Discussionmentioning
confidence: 53%
“…The results obtained in this study highlight the risk of the transmission of this pathogenic mycobacterium to the community. A higher exposition to MAP, which causes a persistent infection in its host [ 44 ], may lead to trigger not only inflammatory bowel diseases including Crohn’s disease [ 44 , 45 ], but also different autoimmune diseases, as it has been previously associated with in several studies [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. This should motivate reflection by legislators and encourage the adoption of the best policies to lower the leakage of this bacterium into communities.…”
Section: Discussionmentioning
confidence: 99%
“…IgE was increased in both indicated allergic reaction by adding adjuvant (Cossu et al, 2017). Elfiky et al (2023) by histopathology & immunology found that bee venom by intradermal injection in 0.1mg in aqueous solution was safe without side effects.…”
Section: Discussionmentioning
confidence: 98%